HUBUNGAN TINGAKT PENGETAHUAN MASYARAKAT TENTANG VAKSIN COVID-19 DENGAN KESEDIAAN MELAKUKAN VAKSIN - RIZKY YUSFASARI; TAUFIK AKBAR FARIED LUBIS (JURNAL ILMIAH KOHESI, 2023)
Coronavirus Disease (COVID-19) is an infection of the respiratory tract caused by the Severe Acute Respiratory SyndromeCoronavirus-2 (SARS CoV-2) virus which first appeared in Wuhan in December 2019. Protective behavior is the key toovercoming the COVID-19 pandemic , and vaccines are one of the main protections to reduce the transmission rate ofCOVID-19. A COVID-19 vaccine is a global public health necessity to stem the pandemic. Currently, there is a lot of wronginformation and public perception about the COVID-19 vaccine. This is related to the side effects of administering thevaccine, which have been linked to several cases of death due to the COVID-19 vaccine. The public's low interest invaccinating against COVID-19 is due to lack of knowledge and many opinions about the COVID-19 vaccine whose truth isunknown. To determine the relationship between the level of public knowledge about the COVID-19 vaccine and willingnessto take the vaccine. The analytical descriptive method was carried out on 284 respondents. The level of public knowledgeregarding the COVID-19 vaccine was 40.8% had good knowledge, 28.5% had sufficient knowledge, and 30.6% had poorknowledge. The public's willingness to vaccinate against COVID-19 is 81% willing and 19% are not willing. After carrying outthe test, the P value was 0.00, so the P value was <0.05, indicating that there was a significant relationship between the levelof knowledge and the willingness to vaccinate the community. There is a relationship between the level of knowledge and thewillingness to vaccinate the community